Risk of Severe Acute Maternal Morbidity According to Planned Mode of Delivery in Twin Pregnancies. Issue 3 (September 2018) - Korb, Diane; Deneux-Tharaux, Catherine; Seco, Aurélien; Goffinet, François; Schmitz, Thomas
Abstract : OBJECTIVE: To evaluate the association between the planned mode of delivery and severe acute maternal morbidity in women with twin pregnancies. METHODS: In this planned secondary analysis of the JUmeaux MODe d'Accouchement cohort, a national prospective population-based study of twin deliveries conducted from February 2014 to March 2015 in 176 hospitals performing more than 1, 500 annual deliveries in France, we included women with twin pregnancies at 24 weeks of gestation or greater with two live fetuses. Women delivering before 24 weeks of gestation, those with recognized indications for cesarean delivery, and those with severe acute maternal morbidity symptomatic before labor were excluded to limit confounding by indication. The primary outcome was a composite measure of intra- or postpartum severe acute maternal morbidity. Multivariate Poisson regression models and propensity score matching were used to control for potential confounding by indication. Analyses were conducted for the overall study cohort as well as stratified by maternal age in years (younger than 30, 30–34, 35 years or older). No adjustments were made for multiple comparisons. RESULTS: Among the 8, 124 women included in this analysis, 3, 062 (37.7%) had planned cesarean deliveries and 5, 062 (62.3%) had planned vaginal deliveries, of whom 4, 015 (79.3%) delivered both twins vaginally. No significant overall association was found between the planned mode of delivery and severe acute maternal morbidity (6.1% in the planned cesarean delivery group and 5.4% in the planned vaginal group; adjusted relative risk 1.00, 95% CI 0.81–1.24). In women 35 years or older, the risk of severe acute maternal morbidity was significantly higher for those with planned cesarean delivery than planned vaginal delivery (7.8% vs 4.6%, adjusted relative risk 1.44, 95% CI 1.02–2.06). Propensity score and secondary analyses yielded similar results. CONCLUSION: In twin pregnancies, there is no overall association between planned mode of delivery and severe acute maternal morbidity. Women older than 35 years may be at higher risk of severe acute maternal morbidity after planned cesarean delivery. Abstract : In twin pregnancies, there is no overall association between planned mode of delivery and severe acute maternal morbidity.